Analysis Utilization Of Online Self-Assessment Application (Aladin) In The Licensing Process Of Clinical And Pharmacy Office Of Investment And One Door Integrated Service In Medan City Year 2021 - Oki Leksmana; Sri Lestari Ramadhani Nasution; Chrismis Novalinda Ginting; Ali Napiah Nasution; Sri Wahyuni Nasution (International Journal of Health and Pharmaceutical (IJHP), 2022)
The use of information and communication technology itself has grown rapidly throughout the world during the COVID-19 pandemic. Developed countries that have succeeded in reducing the number of COVID-19 cases have used various methods of using information and communication technology. Such as the use of tracking applications installed on cellular phones, payments using mobile payment applications, the installation of infrared heat detection cameras at the entrances of public places and crowds, even smart watches with applications that can collect data on heart rate, body temperature, and sleep patterns to detect signs of viral illness.The purpose of this study was to analyze the use of the Online Self-Assessment Application (Aladin) in the licensing process for clinics and pharmacies at the Medan City Investment and One Stop Integrated Service Office in 2021.This research is a descriptive type with a quantitative approach. In this survey research, a questionnaire is used as a research instrument, in the form of a sheet containing several questions with a standard structure as a research instrument. Based on the results of research from several journals using TAM analysis, it was found that perceived ease of use and perceived usefulness had a positive and significant effect on attitudes toward using and actual system use. Their research results show that perceived ease of use and perceived usefulness have a positive and significant effect on attitudes toward using and actual system use.